Diabetes incidence does not differ between subjects with and without high depressive symptoms — 5‐year follow‐up results of the Heinz Nixdorf Recall Study. Issue 1 (13th December 2012) - Icks, A.; Albers, B.; Haastert, B.; Pechlivanis, S.; Bokhof, B.; Slomiany, U.; Erbel, R.; Jöckel, K.‐H.; Kruse, J.; Nowotny, B.; Herder, C.; Giani, G.; et al.
<x xml:space="preserve">Abstract</x> Diabet. Med. 30, 65–69 (2013) Abstract Aims Cross‐sectional studies have consistently reported evidence for an association between diabetes and depressive disorders. However, only limited prospective studies have examined this association, reporting conflicting results. In a population‐based cohort study, we compared cumulative incidences of diabetes between participants with and without high depressive symptoms. Method We analysed the 5‐year follow‐up data from the German Heinz Nixdorf Recall study of 3547 participants without diabetes at baseline [mean age 58.8 (sd 7.6) years, 47.5% male]. Depressive symptoms were defined using the Centre for Epidemiologic Studies Depression scale (cut point ≥ 17). Diabetes (diagnosed or previously undetected) was identified by self‐reported physician‐diagnosed diabetes, medication and high blood glucose levels. We estimated 5‐year cumulative incidences with 95% confidence intervals and fitted multiple logistic regression models to calculate the odds ratios, adjusted for age, sex, physical activity, smoking, living with or without partner, and educational level. Results The cumulative incidence of diabetes was 9.2% (95% CI 6.3–12.8) in participants with high depressive symptoms at baseline and 9.0% (95% CI 8.0–10.0) in participants without these symptoms. The age‐ and sex‐adjusted odds ratio of diabetes in participants with depressive symptoms compared with those without was 1.13 [95% CI 0.77–1.68; fully adjusted 1.11 (95% CI 0.74–1.65)]. These results did not substantially change in several additional sensitivity analyses. Conclusion Our study did not show a significantly increased risk of developing diabetes in individuals with high depressive symptoms compared with those without high depressive symptoms during a 5‐year follow‐up period.